Quantifying the morphology of eyeballs with posterior staphyloma with Zernike polynomials - Rong, Hua; Liu, Lin; Liu, Yuling; Fu, Wanzeng; Xu, He; Yu, Danyang; Wu, Di; Du, Bei; Zhang, Xuejun; Zhang, Bin; Wei, Ruihua (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: To quantify the morphology of eyeballs with posterior staphyloma (PS) with Zernike decomposition and to explore the association between Zernike coefficients with existing PS classification. Methods: Fifty-three eyes with high myopia (HM, ≤-6.00D) and 30 with PS were included. PS was classified with traditional methods based on OCT findings. Eyeballs’ morphology was obtained with 3D MRI, from which the height map of the posterior surface was extracted. Zernike decomposition was performed to derive the coefficients of the 1st-27th items, which were compared between HM and PS eyes with the Mann-Whitney-U test. Receiver operating characteristics (ROC) analysis was used to test the effectiveness of using Zernike coefficients to discriminate PS from HM. Results: Compared to HM eyeballs, PS eyeballs had significantly increased vertical and horizontal tilt, oblique astigmatism, defocus, vertical and horizontal coma, and higher order aberrations (HOA) (all Ps < 0.05). HOA was the most effective in PS classification with an area under the ROC curve (AUROC) value of 0.977. Among the 30 PS, 19 were the wide macular type with large defocus and negative spherical aberration; 4 were the narrow macular type with positive spherical aberration; 3 were inferior PS with greater vertical tilt, and 4 were peripapillary PS with larger horizontal tilt. Conclusions: PS eyes have significantly increased Zernike coefficients, and HOA is the most effective parameter to differentiate PS from HM. The geometrical meaning of the Zernike components showed great accordance with PS classification.